2016
DOI: 10.1016/j.envres.2016.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function and short-term exposure to residential air temperature: A repeated measures study based on spatiotemporal estimates of temperature

Abstract: Few studies have examined the association between ambient temperature and cognitive function, or used exposure to temperature at a given address instead of a single stationary monitor. The existing literature on the temperature-cognition relationship has mostly consisted of experimental studies that involve a small sample size and a few specific temperature values. In the current study, we examined the association between residential air temperature and Mini-Mental State Examination (MMSE) scores, a quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 34 publications
2
42
2
Order By: Relevance
“…Studies have demonstrated that short-term exposure to acute low temperature leads to a decline in cognitive function in young adults [29][30][31] as well as in older adults [16]. However, we did not observe this association.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that short-term exposure to acute low temperature leads to a decline in cognitive function in young adults [29][30][31] as well as in older adults [16]. However, we did not observe this association.…”
Section: Discussioncontrasting
confidence: 99%
“…Most relevant research focuses on young people rather than on older adults. In a longitudinal cohort study of older men, short-term exposure to higher air temperatures was signi cantly associated with low scores on the Mini-Mental State Examination [16]. Our nding of an association between short-term exposure to higher temperatures and moderate-to-severe cognitive impairment in community-dwelling older adults was consistent with those of other studies.…”
Section: Discussionsupporting
confidence: 90%
“…The higher relative risks found for the older age-group might be associated with a higher prevalence of cognitive problems among the older population. Previous studies have reported negative associations between temperature and cognitive function among Japanese [ 45 ] and Americans [ 46 ], while another study from Massachusetts, USA reported an U-shaped association with cognitive function and identified minimum risk at 10–15 °C [ 47 ]. Our study also found a U-shaped association between temperature and dementia admissions, although the association was nonsignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Measures of emotional and cognitive states are also impacted by temperatures (Connolly, 2013;Noelke et al, 2016;Baylis et al, 2018;Dai et al, 2016;Graff Zivin et al, 2018). Temperature-driven behavior alterations may either be indicate or contribute to such changes in emotional/cognitive states.…”
Section: Related Researchmentioning
confidence: 99%